Early and late gene expression profiles of the ovine mucosa in response to Haemonchus contortus infection employing Illumina RNA-seq technology. Issue 5 (October 2017) - El-Ashram, Saeed; Al Nasr, Ibrahim; El-Kemary, Maged; Mehmood, Rashid; Hu, Min; Suo, Xun
Abstract: We conducted herein transcriptome sequencing of the ovine abomasal tissues using the Illumina HiSeq 4000 platform to segregate early and late H. contortus -infected sheep (7 and 50 days post-infected groups, respectively) from the control naive ones. A total of 548, 357 and 7 were substantially induced genes in 7 days post-infection versus uninfected-control group, 50 days post-infection versus 7 days post-infection (7 dpi), and 50 days post-infection (50 dpi) versus uninfected-control group, respectively. However, a total of 301, 355 and 11 were significantly repressed genes between 7 dpi versus uninfected-control group, 50 dpi versus 7 dpi, and 50 dpi versus uninfected-control group, correspondingly. This indicates that H. contortus infection induced a more potent activation of abomasal gene expression in the early stage of infection as compared to the late stage. Seven pathways were annotated by Kyoto Encyclopedia of Genes, and Genomes pathway analysis accounted for the significant percentage in early H. contortus infection. This study shows for the first time that both galectin-11 and matricellular protein osteopontin are up-regulated in abomasal tissue after chronic H. contortus infection, while galectin-4 is specifically down-regulated in the early infection. Additionally, our results showed that the induction or repression of these molecules is likely to determine the infection progression.